PERLIDUNGAN HUKUM TERHADAP PELAKSANAAN KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PERUSAHAAN - Erni Darmayanti (JCH (Jurnal Cendekia Hukum), 2018)
Legal protection concerning Occupational Safety and Health at company, given in effort of prevention (preventive) to avoid accident and cause work-related diseases. The Importance of Occupational Safety and Health is closely related to employee performance and ultimately affects the company's performance. In this case, this study discusses: First, general understanding of Occupational Safety and Health (K3), Second, How is the protection of law regarding Occupational Safety and Health (K3) according to the laws and regulations in Indonesia. This research is a normative juridical research with secondary data collection method that is research of library (library research) in the form of primary law material, secondary law material and tertiary legal material. The results of this study explain that the safety of work on the company is included in the technical protection, where the protection of the worker in question is for workers to be safe from the harm that can be caused by work tools or materials and work health which is also intended to protect or keep workers from the events harm health and decency in doing his job. Implementation Legal protection of Occupational Safety and Health in legislation in accordance with Law No. 1 of 1970 on Occupational Safety and Law No. 13 of 2003.